TRENDS IN SELECTIVE COLLECTION OF THE HOUSEHOLD WASTE - Baltes, Liana; Draghici, Camelia; Manea, Camelia; Ceausescu, Dan; Tierean, Mircea (OAIMDD - EcoZone Publishing House, 2009)
The paper presents actual trends concerning the selective collection of the household waste. The collecting methods used in the EU countries and the results obtained by the Romanian municipalities in the last two years are also exposed. The results show the dynamics of household collection and the expectations for the next years. It is known that a town of 100 000 inhabitants collecting 100% of its household recyclable packaging waste could recycle 780 tonnes of steel, 200 tonnes of aluminium, 470 tonnes of plastics, 2300 tonnes of paper and 2200 tonnes of glass per year (Bio Intelligence Service S.A.S., 2005). This is why it is important that local authorities implement an efficient waste collection system, which enables them to maximize the recyclable packaging collected with minimum environmental impacts and costs
Keywords: recyclingselective collectionwaste